Securitisation, Scapegoat, Identity Politics: Why Did President Duterte Mark Record-High Approval Ratings Despite His Failure to Combat the COVID-19 Pandemic? - Kenki Adachi (Journal of Current Southeast Asian Affairs)
This paper delves into the Philippines’ response to the COVID-19 pandemic, focusing on the enforcement of a rigorous lockdown and the paradoxical rise in President Rodrigo Duterte's approval despite the virus's unmitigated spread. While conventional analyses lean on securitisation to explain military involvement in pandemic control, this paper argues that COVID-19 was not securitised in the Philippines. Instead, the government targeted the “pasaway” (undisciplined) as a supposed threat to national security, employing identity politics. By presenting the undisciplined as adversaries, the government garnered support from perceived “good citizens.” Despite human rights concerns and a lack of evidence linking the undisciplined to virus transmission, the narrative of cracking down on them garnered widespread approval. This challenges traditional securitisation explanations, suggesting that the emphasis on a “scapegoated enemy” and identity politics played a pivotal role in shaping public perception and elevating presidential approval ratings.